Pemanfaatan Tenaga Surya Untuk Penerangan Di Desa Oro-Oro Ombo (TEKAD : Teknik Mengabdi, 2024)
Oro-Oro Ombo Village is located in the Batu Malang area, East Java, Indonesia, and is famous for its culture, architecture, and beautiful environment. Located on the hillside of Panderman Mountain, this village has a landscape dominated by terraced rice fields, vegetable gardens, and fruit orchards. This village is located on a plateau with winding roads, many rivers, and trees which make agriculture and plantations the livelihood of most of the village residents. However, the lack of street lighting in this area can raise security concerns for residents who are active at night. Apart from that, the problem of minimal education regarding waste processing is a matter of concern, so there is a need for education and outreach regarding this matter to increase public awareness and understanding regarding sustainable waste management practices. To overcome the problem of street lighting, a community service activity will be carried out to design and construct street lighting in Oro Oro Ombo Village by utilizing solar energy as an alternative energy. This activity also includes training and mentoring village residents to understand the working principles of solar power plants, so that residents can carry out the necessary maintenance. Street lighting aims to improve public safety, promote economic development, and improve the overall quality of life in rural areas.